Single-source precursor deposition of low-toxicity sulphides for thin film photovoltaic devices - Bishop, Matthew T. (2019)
Solar power has long been considered as an environmentally friendly method of energy generation, enjoying continued development and implementation. However, silicon solar cells (the most commercially successful type of solar cell) require high energy input for the extraction of silicon, high material quality, and is an economically expensive technology. This thesis investigates the use of alternative solar cells, namely: hybrid solar cells, using both organic and inorganic semiconductors, with an additional study focusing on utilising non-toxic materials for fabricating thin film inorganic solar cells. Overcoming obstacles associated with the future commercialisation of these techniques (i.e. associated toxicity and fabrication challenges) is the main purpose of this work. A key focus will be placed on metal xanthates, utilised as the inorganic precursor for each of these devices, as they have been proven to be effective, low temperature precursors for metal sulphide deposition.